RETRACTED: The Influence Of Job Rotation, Work Environment, And Job Stress On The Performance Of East Jakarta Administrative Satpol Pp - Dewi Ambarsari; Herry Krisnandi; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This study aims to analyze how much influence the work rotation, physical work environment and work stress on performance. This Study used primary data by distributing questionaires of 92 respondents and the respondents are SATPOL PP in the administration city of east Jakarta. Data were analyzed using Multiple Linear Regression Correlation analysis. The results showed a positive and significant effect on performance, which is shown in the Coefficients table in the regression equation model Y = 6.373 + 0.197 + 0.390 + 0.126. The feasibility test results of the model shown with a significance value of 0,000 shown in the ANOVA table which means that the model in this study is feasible based on the significance value obtained. And the conclusion of the hypothesis by t-test partially obtained the significance value on the variable work rotation by 0.038, then on the physical work environment variable at 0,000, and the significance on the brand image variable at 0.049. Then it is concluded that the three independent variables partially have a significant influence on the dependent variable. In order for the management of related agencies to pay more attention to the work environment that has the greatest contribution value and to be better at managing work rotation policies and procedures as well as maintaining work stress conditions to its members so that employees are more motivated to provide the best performance, which will have an impact on achieving common goals.